Thermal effects on the strain rate-dependent behavior of highly compacted GMZ01 bentonite - Pengju Qin; Weimin Ye; Qiong Wang; Yonggui Chen (Journal of Rock Mechanics and Geotechnical Engineering)
Investigation of thermal effects on the strain rate-dependent properties of compacted bentonite is crucial for the long-term safety assessment of deep geological repository for disposal of high-level radioactive waste. In the present work, cylindrical GMZ01 bentonite specimens were compacted with suction-controlled by the vapor equilibrium technique. Then, a series of temperature- and suction-controlled stepwise constant rate of strain (CRS) tests was performed and the rate-dependent compressibility behavior of the highly compacted GMZ01 bentonite was investigated. The plastic compressibility parameter λ, the elastic compressibility parameter κ, the yield stress p0, as well as the viscous parameter α were determined. Results indicate that λ, κ and α decrease and p0 increases as suction increases. Upon heating, parameters λ, α and p0 decrease. It is also found that p0 increases linearly with increasing CRS in a double-logarithm coordinate. Based on the experimental results, a viscosity parameter α(s, T) was fitted to capture the effects of suction s and temperature T on the relationship between yield stress and strain rate. Then, an elastic-thermo-viscoplastic model for unsaturated soils was developed to describe the thermal effects on the rate-dependent behavior of highly compacted GMZ01 bentonite. Validation showed that the calculated results agreed well to the measured ones.